Nutrigenomics - Sonkar, Seema; Singh, Richa (Recent Updates in Disease and Health Research Vol. 7, 2024)
Recent developments in the field of nutrigenomics are advancing nutrition research and creating new paradigms. "Nutrigenomics" is the application of genomic principles to the discovery of associations between certain nutrients and genetic variables. Addressing the risk factors for chronic degenerative diseases linked to nutrition is crucial in order to address the underlying mechanism of hereditary predisposition. The development of a profound understanding of genetic variations and gene expression patterns has been made possible by advances in the sciences related to the study of genes. This understanding has helped to develop treatment responses for chronic degenerative disorders linked to public health. Nutrigenomics information aids in developing individualized nutrition plans for disease treatment and disease prevention.